New developments in anaerobic and aerobic athletic training - Cedaro, R.
A Quick Review The human body can produce energy in one of three ways; two of these pathways are "anaerobic" in nature (i.e. not requiring oxygen for energy metabolism), the third - the aerobic - produces energy at a much slower rate but for extended periods of time in the presence of oxygen. One of the most fundamental mistakes made by coaches and athletes alike when training for competition is that they look at these different energy systems in isolation. The fact of the matter is that each of these systems work in concert with one another, rather than in a mutually exclusive manner. The task of a well prepared coach is to understand the energy demands of his/her athletes' event, coupled with their athletes' specific strengths and weaknesses and train to prepare the athletes for that particular event by training the energy systems in an appropriate manner to optimise performance. Knowing the demands of the sport/event alone is not enough. The coach must also have an intimate understanding of his/her athletes' physiological and psychological make-up to enable appropriate training loads to be set. For the sake of simplicity let's look at training advances from aerobic and anaerobic perspectives and then see how to integrate the whole process. Training Loads For years physiologists believed that athletes either trained aerobically (i.e. Less than individual anaerobic threshold "I.A.T.") or anaerobically (i.e. Higher than I.A.T.). More recent research has shown that there are five distinct exercise intensities that evoke specific physiological responses in athletes: Level One Exercise Intensity (L1): The athlete exercises at 70-75% of the I.A.T. heart rate. This training is designed as "active recovery" to help flush waste metabolites from the working musculature after competition or a hard training session and stimulate the delivery of fresh, oxygenated blood and nutrients back to the fatigued muscles. Such a training intensity typically produces a blood lactate concentration of between 0.5 to 1.5 mM. Level Two Exercise Intensity (L2): Here the athlete exercises at 80-85% of I.A.T. heart rate. This type of training load is designed to stimulate "peripheral cardiovascular fitness" by increasing muscular capillarization, increasing the concentration of aerobic enzymes, improving fat metabolism, increasing glycogen storage capacity, increasing the concentration of mitochondria (i.e. Aerobic energy houses) within the trained muscles and as such, eventually, allowing the athlete to stay aerobic at higher workloads than could be achieved previously. Such training typically evokes blood lactate concentrations of 2-3 mM. Level Three Exercise Intensity (L3): Here the athlete works at 95-100% of I.A.T. heart rate and the training is designed to stimulate the "central" component of the cardiovascular fitness equation by increasing lactate production to the point at which the rate of production is matched by clearance. Research has shown consistently that training at the "anaerobic threshold" has the most significant effect on increasing cardiovascular fitness. Here lactate concentrations are within the range of 4-7 mM. Level Four Exercise Intensity (L4): The athlete exceeds the I.A.T. (i.e. 105%+ of I.A.T. heart rate) and takes lactate production beyond that which can be comfortably cleared to sustain the same exercise intensity. Here the athlete works at levels which exceed their ability to clear the produced lactate. As a result lactic acid begins to accumulate eventually forcing the athlete to slow down in order to dissipate this by-product of anaerobic metabolism. By doing a certain limited amount of weekly training at this intensity the athlete enhances his/her ability to "tolerate" this lactic acid load before being forced to decrease exercise intensity (i.e. slow down). By raising lactate loads to maximal or near maximal concentrations the athlete enhances their ability to metabolise this metabolite thus enhancing central cardiovascular fitness as 75% of lactate produced is metabolised by cardiac muscle. During this form of training blood lactate concentrations should be close to maximal. Level Five Exercise Intensity (L5): The ATP-PC, or instantly available energy system within the muscles (i.e. The alactic energy system) is the central focus of this training intensity. The ATP-PC system provides great concentrations of energy quickly, as the energy is stored within the muscles, however this energy source is very quickly exhausted (within 8-15 seconds). It is important that aerobic based athletes (e.g. triathletes) maintain this energy system as it will be drawn upon in competition (e.g. Surging out of the saddle on the bike to clear a small hill without losing one's momentum). If the system's not trained the athlete wont be able to call upon it effectively during competition. Research has shown that by working at different exercise intensities different physiological responses can be evoked. The mistake often made by many aerobic based endurance sport athletes is that they train or race too hard too often. Sending the body beyond the I.A.T. (or L3 exercise intensity) too frequently actually has detrimental effects upon aerobic metabolism (i.e. High concentrations of lactic acid actually decrease fat metabolism, adversely effecting cellular membrane integrity and aerobic enzyme function). Therefore a fine balance must be struck between enough "quality" work to increase I.A.T. and too much which will suppress aerobic function and often result in chronic fatigue. For example, a mature triathlete preparing for an upcoming ironman in six months may structure their run training routine in the following manner: Base Training Phase: 3 months: 140-160 kilometres per week. Exercise intensity L1 30% L2 60% L3 10% L4 0% L5 0% Intermediate Training Phase: 2 months: 120-140 kilometres per week. Exercise intensity L1 20% L2 50% L3 20% L4 10% L5 0%